2009
DOI: 10.1111/j.1469-7610.2008.02050.x
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of genes and early mother–child relationship in the development of self‐regulation from toddler to preschool age

Abstract: Background-A broad capacity for deliberate self-regulation plays a key role in emotion regulation. This longitudinal investigation from infancy to preschool age examines genotype by environment (G × E) interaction in the development of self-regulation, using molecular measures of children's genotypes and observed measures of the quality of early mother-child relationship, as reflected in attachment organization in infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
165
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(174 citation statements)
references
References 57 publications
6
165
1
2
Order By: Relevance
“…Here, the effect of attachment at 4 years of age only came out significant with parent reports. Given that previous studies have reported Attachment ϫ 5-HTTLPR effects in preschoolers (Kochanska et al, 2009) and adolescents (Starr et al, 2013;Zimmermann et al, 2009), our mixed GXE results at 6 years of age may be methodological rather than substantial. Notwithstanding, our results discerned a main effect of the SS genotype on emotion regulation at 8 years of age.…”
Section: Differential Susceptibility and 5-httlprmentioning
confidence: 85%
See 3 more Smart Citations
“…Here, the effect of attachment at 4 years of age only came out significant with parent reports. Given that previous studies have reported Attachment ϫ 5-HTTLPR effects in preschoolers (Kochanska et al, 2009) and adolescents (Starr et al, 2013;Zimmermann et al, 2009), our mixed GXE results at 6 years of age may be methodological rather than substantial. Notwithstanding, our results discerned a main effect of the SS genotype on emotion regulation at 8 years of age.…”
Section: Differential Susceptibility and 5-httlprmentioning
confidence: 85%
“…As a result, attachment security, as an environmentally induced regulatory mechanism, could be especially important for the development of emotion regulation among more reactive S carriers. In fact, S carriers have been found to be most affected by their attachment styles with regard to self-regulation in preschool (Kochanska et al, 2009), as well as autonomy and aggression (Zimmermann, Mohr, & Spangler, 2009) and stress and depression (Starr, Hammen, Brennan, & Najman, 2013) in adolescence. Whereas the research by Kochanska et al (2009) proved consistent with the diathesisstress model, the work of Starr et al (2013) and Zimmermann et al (2009) appears more consistent with differential-susceptibility theorizing.…”
Section: The Moderating Role Of 5-httlprmentioning
confidence: 99%
See 2 more Smart Citations
“…In the other words, executive functioning is shaped (thus influenced) by a complex interplay between these factors (25,26). Evidence suggests that parents' guidance is one of the primary experiences contributing to children's executive function during early childhood (27).…”
Section: Discussionmentioning
confidence: 99%